Implementation of Canva-Based History Card Learning Media to Improve Social Studies Learning Outcomes in Grade VIII A of SMP Negeri 16 Palu - Hermawan, Wingky; Suyuti; Gammar, Mahfud M.; Windayanti (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
This study aims to determine whether the application of Canva-based History Card learning media can improve student learning outcomes in class VIII A of SMP Negeri 16 Palu in social studies learning. This study uses the Classroom Action Research (CAR) method with a cycle-based approach from Kemmis and McTaggart which is implemented in two cycles with the use of Canva-based History Card learning media in the learning process, each consisting of the following stages: (1) planning, (2) action, (3) observation, and (4) reflection. This data collection uses written tests in the form of pre-tests and post-tests. The results of the study showed a significant increase in student learning outcomes. In cycle I, only 8 students achieved the Minimum Completion Criteria (KKM) with a percentage of 32%, while in cycle II it increased to 19 students with a percentage of 76%. In addition, the use of History Cards is also able to increase student enthusiasm, focus, and active involvement during learning. Thus, it can be concluded that the use of Canva-based History Card learning media is effective in improving student learning outcomes in social studies learning.